Block copolymer, polymer electrolyte material using said block copolymer, polymer electrolyte molded article, polymer electrolyte membrane, electrolyte membrane with catalyst layer, membrane electrode composite, solid
By adjusting the molecular weight of ionic and nonionic chain segments in the block copolymer, a specific aromatic hydrocarbon-based polymer block copolymer was designed, which solved the problem of insufficient power generation performance and mechanical strength under low humidification conditions in the prior art, and achieved efficient power generation performance and mechanical strength.
Patent Information
- Application Number
- CN202380062709.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-06
- Publication Date
- 2025-04-11
AI Technical Summary
The existing block copolymers have incomplete power generation performance and mechanical strength improvement effects under low humidification conditions, making it difficult to meet the requirements of industrial applications.
By adjusting the molecular chain lengths of the chain segments containing ionic groups and the chain segments containing no ionic groups, block copolymers of aromatic hydrocarbon-based polymers with a number average molecular weight exceeding 40,000 and less than 50,000 were designed, and the relationship between Mn3/(Mn1+Mn2)>1.5 was met.
It has achieved excellent power generation performance, mechanical strength and physical durability under low humidification conditions, and also excellent processability.
Smart Images

Figure BDA0005289755220000031 
Figure BDA0005289755220000032 
Figure BDA0005289755220000061
Abstract
Description
Technical Field
[0001] The present invention relates to a block copolymer, a polymer electrolyte material using the block copolymer, a polymer electrolyte molded body, a polymer electrolyte membrane, an electrolyte membrane with a catalyst layer, a membrane electrode complex, a solid polymer fuel cell and a water electrolysis type hydrogen generation device. Background Art
[0002] Fuel cells are a type of power generation device that extracts electrical energy by electrochemically oxidizing fuels such as hydrogen and methanol. In recent years, they have attracted attention as a clean energy supply source. Among them, solid polymer fuel cells are expected to be widely used as power generation devices for smaller-scale distributed power generation facilities, automobiles, ships and other mobile bodies because their standard operating temperature is as low as about 100°C and their energy density is high. In addition, solid polymer fuel cells are also attracting attention as power sources for small mobile devices and portable devices, and are also expected to be used as a substitute for secondary batteries such as nickel-metal hydride batteries and lithium-ion batteries in mobile phones and personal computers.
[0003] Fuel cells are usually constructed with a membrane electrode assembly (MEA) sandwiched by separators as a unit. MEA has catalyst layers on both sides of the electrolyte membrane, and gas diffusion layers on both sides thereof. In MEA, a pair of electrode layers are formed by catalyst layers and gas diffusion layers sandwiching the electrolyte membrane and arranged on both sides, one of which is the anode electrode and the other is the cathode electrode. Electricity is produced through electrochemical reactions by contacting the anode electrode with a fuel gas containing hydrogen and contacting the cathode electrode with air. The electrolyte membrane is mainly composed of polymer electrolyte materials. Polymer electrolyte materials are also used as binders for catalyst layers.
[0004] In the past, as a polymer electrolyte material, "NAFION" (registered trademark) (manufactured by Kemazu Co., Ltd.), which is a fluorine-based polymer electrolyte, has been widely used. On the other hand, the development of hydrocarbon-based electrolyte materials that are cheap and have excellent membrane properties and can replace "NAFION" (registered trademark) has also been active in recent years. Hydrocarbon-based electrolyte materials have low gas permeability and excellent heat resistance, and electrolyte materials using aromatic polyether ketones and aromatic polyether sulfones have been particularly actively studied. However, conventional hydrocarbon-based electrolyte materials show power generation performance that is equal to or superior to that of fluorine-based electrolyte materials under high humidification conditions, but on the other hand, the power generation performance under low humidification conditions is insufficient.
[0005] As a hydrocarbon-based polymer electrolyte material having excellent power generation performance even under low humidification conditions and excellent mechanical strength and chemical stability, a block copolymer composed of a segment containing an ionic group (hereinafter referred to as an "ionic segment") and a segment not containing an ionic group (hereinafter referred to as a "non-ionic segment") has been proposed (for example, see Patent Documents 1 to 2). In particular, Patent Document 2 discloses an aromatic polyethersulfone using a segment with a number average molecular weight of 80,000 as an ionic segment.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2013 / 002274
[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-109638 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, even when the block copolymers described in Patent Documents 1 and 2 are used, the effects of improving power generation performance and mechanical strength under low humidity conditions are not complete, and further improvements are desired as industrially useful block copolymers and polymer electrolyte materials using the block copolymers.
[0012] In view of the background of the prior art, the present invention aims to realize a block copolymer having excellent power generation performance even under low humidity conditions, excellent mechanical strength and physical durability, and excellent processability, and a polymer electrolyte material using the block copolymer.
[0013] Means for solving problems
[0014] The present inventors have conducted intensive studies on the above-mentioned problems and have found that by appropriately adjusting the molecular chain lengths of the segments containing ionic groups and the segments containing no ionic groups, a block copolymer having improved power generation performance under low humidity conditions and excellent processability can be obtained.
[0015] The present invention has the following configurations.
[0016] [1] A block copolymer having one or more segments containing an ionic group (hereinafter referred to as "ionic segments") and one or more segments not containing an ionic group (hereinafter referred to as "non-ionic segments"), wherein the ionic segments are aromatic hydrocarbon polymers having a number average molecular weight of more than 40,000 and less than 50,000, and when the number average molecular weight of the ionic segments is set to Mn1, the number average molecular weight of the non-ionic segments is set to Mn2, and the number average molecular weight of the block copolymer is set to Mn3, the relationship of Mn3 / (Mn1+Mn2)>1.5 is satisfied.
[0017] [2] The block copolymer according to [1], wherein the heat of crystallization of the block copolymer measured by differential scanning calorimetry is 0.1 J / g or more, or the degree of crystallinity of the block copolymer measured by wide-angle X-ray diffraction is 0.5% or more.
[0018] [3] The block copolymer according to [1] or [2], wherein the aromatic hydrocarbon polymer is an aromatic polyether polymer.
[0019] [4] The block copolymer according to [3], wherein the aromatic polyether polymer is an aromatic polyether ketone polymer.
[0020] [5] The block copolymer according to any one of [1] to [4], wherein the block copolymer has a linker site that bonds the ionic segment and the nonionic segment.
[0021] [6] The block copolymer according to any one of [1] to [5], which has a relationship of 2<Mn1 / Mn2<7.
[0022] [7] The block copolymer according to any one of [1] to [6], wherein the ionic segment includes a structure represented by the following general formula (S1).
[0023] *-Ar1-Y 1 -Ar 2 -O-Ar 3 -Y 2 -Ar 4 -O-* (S1)
[0024] (In the general formula (S1), Ar 1 ~Ar 4 Each independently represents a substituted or unsubstituted arylene group, Ar 1 ~Ar 4 At least one of them has an ionic group. 1 and Y 2Each independently represents a keto group or a protective group that can be derived into a keto group. * represents a bond to the general formula (S1) or other structural units.
[0025] [8] The block copolymer according to [7], wherein the structure represented by the general formula (S1) is a structure represented by the following general formula (S2).
[0026]
[0027] (In general formula (S2), Y 1 and Y 2 Each independently represents a keto group or a protective group capable of being derived into a keto group. 1 ~M 4 Each independently represents a hydrogen atom, a metal cation or an ammonium cation. n1 to n4 are each independently 0 or 1, and at least one of n1 to n4 is 1. * represents a bond with the general formula (S2) or other structural units.
[0028] [9] The block copolymer according to any one of [1] to [8], wherein the nonionic segment contains an aromatic polyether polymer.
[0029]
[10] The block copolymer according to [9], wherein the aromatic polyether polymer is an aromatic polyether ketone polymer.
[0030]
[11] The block copolymer according to any one of [1] to [9], wherein the nonionic segment has a structure represented by the following general formula (S3).
[0031] *-Ar 5 -Y 3 -Ar 6 -O-Ar 7 -Y 4 -Ar 8 -O-* (S3)
[0032] (In general formula (S3), Ar 5 ~Ar 8 Each independently represents an arylene group. 5 ~Ar 8 None of them have ionic groups. 3 and Y 4 Each independently represents a keto group or a protective group that can be derived into a keto group. * represents a bond to the general formula (S3) or other structural units.
[0033]
[12] The block copolymer according to
[11] , wherein the structure represented by the general formula (S3) is a structure represented by the following general formula (S4).
[0034]
[0035] (In general formula (S4), Y 3 and Y 4 Each independently represents a keto group or a protective group that can be derived into a keto group. * represents a bond to the general formula (S4) or other structural units.
[0036]
[13] The block copolymer according to any one of [1] to
[12] , which has a co-continuous phase separation structure.
[0037]
[14] A polymer electrolyte material comprising the block copolymer according to any one of [1] to
[13] .
[0038]
[15] A polymer electrolyte molded body comprising the polymer electrolyte material described in
[14] .
[0039]
[16] A polymer electrolyte membrane formed using the polymer electrolyte material described in
[14] .
[0040]
[17] An electrolyte membrane with a catalyst layer, which is formed using the polymer electrolyte membrane described in
[16] .
[0041]
[18] A membrane electrode assembly, which is formed using the polymer electrolyte membrane described in
[16] .
[0042]
[19] A solid polymer fuel cell, which is constructed using the polymer electrolyte membrane described in
[16] .
[0043]
[20] A water electrolysis hydrogen generation device, which is constructed using the polymer electrolyte membrane described in
[16] .
[0044] Effects of the Invention
[0045] The block copolymer of the present invention exhibits excellent processability as a block copolymer by appropriately controlling the molecular weight of the segments forming the blocks, and can have both good physical durability and high power generation performance including under low humidity conditions as a polymer electrolyte material.
[0046] In the present invention, good mechanical strength and physical durability refer to good dimensional stability, and good dimensional stability refers to a small dry-wet dimensional change rate. The dry-wet dimensional change rate can be measured by the method described in the Examples. DETAILED DESCRIPTION
[0047] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with various modifications depending on the purpose and application.
[0048] [Block copolymer]
[0049] The block copolymer of the present invention is a block copolymer having one or more ionic segments and one or more non-ionic segments, wherein the ionic segments are aromatic hydrocarbon polymers having a number average molecular weight greater than 40,000 and less than 50,000, and when the number average molecular weight of the ionic segments is set to Mn1, the number average molecular weight of the non-ionic segments is set to Mn2, and the number average molecular weight of the block copolymer is set to Mn3, the relationship of Mn3 / (Mn1+Mn2)>1.5 is satisfied.
[0050] In the present invention, the so-called segment is a partial structure of a macromolecular monomer used in the synthesis of a block copolymer in a block copolymer. The block copolymer of the present invention contains a nonionic segment while containing an ionic segment. It should be noted that, in the present invention, although it is recorded as a nonionic segment, the segment can contain a small amount of ionic groups within a range that does not adversely affect the effect of the present invention. Hereinafter, "does not contain an ionic group" and "nonionic" are sometimes used in the same meaning.
[0051] It should be noted that “the above-mentioned ionic segment has an aromatic hydrocarbon polymer having a number average molecular weight of more than 40,000 and less than 50,000” has the same meaning as “the above-mentioned ionic segment has a structure of an aromatic hydrocarbon polymer, and the number average molecular weight of the above-mentioned ionic segment exceeds 40,000 and less than 50,000.”
[0052] The number average molecular weight and weight average molecular weight in the present invention are defined as values measured using gel permeation chromatography (GPC) and calculated in terms of standard polystyrene as described in Examples below.
[0053] When the ionic segment contains a protecting group, the number average molecular weight of the ionic segment before deprotection is defined as Mn1. In addition, when block copolymerization is performed using a precursor of the ionic segment, the number average molecular weight of the ionic segment precursor is defined as Mn1. The number average molecular weight of the ionic segment after deprotection and the number average molecular weight of the ionic segment after conversion from the ionic segment precursor to the ionic segment can be calculated from the structural formula before and after assuming that it is completely deprotected or completely converted from the precursor.
[0054] When the nonionic segment and the block copolymer each contain a protecting group, the number average molecular weight of the nonionic segment before deprotection and the number average molecular weight of the block copolymer before deprotection are defined as Mn2 and Mn3, respectively.
[0055] In the case where Mn1 exceeds 40,000, the polymer electrolyte material including the block copolymer exhibits excellent power generation performance under low humidity conditions.
[0056] In general, power generation performance is related to proton conductivity. Proton conductivity is positively correlated with ion exchange capacity, but the polymer electrolyte material comprising the block copolymer of the present invention, if compared with a block copolymer having an ion exchange capacity of the same degree, shows high proton conductivity when Mn1 exceeds 40,000. Mn1 is preferably more than 42,000, more preferably more than 43,000, further preferably more than 44,000, and particularly preferably more than 45,000. If Mn1 is less than 50,000, the difficulty of synthesis is low, and there is no need for complex steps such as precise adjustment of the amount of monomer added, control of the synthesis temperature, and successive addition of monomers. It can be easily synthesized by general polycondensation reactions and coupling reactions, and has excellent processability.
[0057] Since the crystallinity of the block copolymer increases with the increase of Mn2, and the water resistance and physical durability are improved, Mn2 is preferably 7,000 or more, more preferably 9,000 or more. In addition, Mn2 is preferably 40,000 or less, more preferably 35,000 or less, and particularly preferably 30,000 or less.
[0058] Since the mechanical strength of the block polymer increases with an increase in Mn3, Mn3 is preferably 60,000 or more, more preferably 100,000 or more. The upper limit is preferably 300,000 or less.
[0059] The block copolymer of the present invention, when satisfying the relationship of Mn3 / (Mn1+Mn2)>1.5, forms a phase separation that is advantageous for both proton conductivity and mechanical strength in a polymer electrolyte material containing the block copolymer, and can have both high power generation performance and durability under low humidification conditions. It is more preferred to satisfy the relationship of Mn3 / (Mn1+Mn2)≥1.7, and it is further preferred to satisfy the relationship of Mn3 / (Mn1+Mn2)≥1.9. The upper limit value of Mn3 / (Mn1+Mn2) is preferably 10.0 or less, more preferably 8.0 or less, and further preferably 5.0 or less.
[0060] The block copolymer of the present invention can achieve particularly high power generation performance and mechanical strength when the number average molecular weight of the ionic segment exceeds 40,000 and the above relationship of Mn3 / (Mn1+Mn2)>1.5 is satisfied.
[0061] The block copolymer of the present invention has crystallinity while having a phase separation structure, which is preferred from the viewpoint of dimensional stability and mechanical strength. Generally speaking, dimensional stability, mechanical strength and ion exchange capacity are negatively correlated, but the polymer electrolyte material comprising the block copolymer of the present invention, if compared with block copolymers with the same degree of ion exchange capacity, can achieve high dimensional stability by having crystallinity.
[0062] The presence or absence of crystallinity can be confirmed by differential scanning calorimetry (DSC) or wide-angle X-ray diffraction. Here, it is said that the crystallization heat of the block copolymer measured by differential scanning calorimetry is 0.1J / g or more, or the crystallinity of the block copolymer measured by wide-angle X-ray diffraction is 0.5% or more. That is, in the present invention, the so-called "having crystallinity" refers to any one of being able to crystallize, having the property of being able to crystallize, and having been crystallized if the polymer is heated up. In addition, the so-called amorphous polymer refers to a polymer that is not a crystalline polymer or is not substantially crystallized. Therefore, even if it is a crystalline polymer, when crystallization is not fully performed, as the state of the polymer at that moment, it is sometimes an amorphous state.
[0063] [Ionic segment]
[0064] The block copolymer of the present invention contains an ionic segment having the structure of the above-mentioned aromatic hydrocarbon polymer. The so-called hydrocarbon refers to polymers other than perfluoropolymers, and the so-called aromatic hydrocarbon polymer is a polymer other than perfluoropolymers and is mainly composed of aromatic rings.
[0065] In the present invention, the aromatic ring contained in the aromatic hydrocarbon polymer may include not only a hydrocarbon aromatic ring but also a heterocyclic ring. In addition, a part of the aliphatic unit may constitute a polymer together with the aromatic ring unit. Specific examples of aromatic hydrocarbon polymers include those having a main chain with an aromatic ring selected from polysulfone, polyethersulfone, polyphenylene ether, polyarylene ether polymer, polyphenylene sulfide, polyphenylene sulfide sulfone, polyparaphenylene, polyarylene polymer, polyarylene ketone, polyetherketone, polyarylene phosphine oxide, polyether phosphine oxide, polyphenylene The aromatic hydrocarbon polymer is preferably an aromatic polyether polymer from the viewpoint of cost and polymerizability.
[0066] The so-called aromatic polyether polymer refers to a substance in which, in a polymer mainly composed of aromatic rings, at least an ether bond is included in the repeating unit as a way of connecting aromatic ring units. As the structure of the aromatic polyether polymer, for example, aromatic polyether, aromatic polyether ketone, aromatic polyether ether ketone, aromatic polyether ketone ketone, aromatic polyether ether ketone ketone, aromatic polyether ketone ether ketone ketone, aromatic polyether ketone ether ketone ketone, aromatic polyether imide, aromatic polyether sulfone, etc. can be cited, but it is not limited to these. The above-mentioned aromatic polyether polymer is preferably an aromatic polyether ketone polymer and a polyether sulfone polymer from the perspective of chemical stability and cost, and is most preferably an aromatic polyether ketone polymer from the perspective of mechanical strength, dimensional stability, and physical durability.
[0067] The aromatic polyetherketone polymer refers to a polymer mainly composed of an aromatic ring, which contains at least an ether bond and a ketone bond as a linking form of the aromatic ring units in a repeating unit.
[0068] The aromatic polyethersulfone polymer refers to a polymer mainly composed of an aromatic ring, which contains at least an ether bond and a sulfone bond as a linking form of the aromatic ring units.
[0069] As a method for adjusting Mn1 to more than 40,000 and less than 50,000, the method is not particularly limited as long as the target molecular weight can be achieved. There are methods for synthesizing chain segments by aromatic nucleophilic substitution reaction and coupling reaction, but synthesis by aromatic nucleophilic substitution reaction is preferred from the perspective of ease of process.
[0070] It is preferred that the ionic segment of the block copolymer of the present invention has a structure represented by the following general formula (S1) from the viewpoints of dimensional stability, mechanical strength, and chemical stability.
[0071] *-Ar 1 -Y 1 -Ar 2 -O-Ar 3 -Y 2 -Ar 4 -O-* (S1)
[0072] In the general formula (S1), Ar 1 ~Ar 4 Each independently represents a substituted or unsubstituted arylene group, Ar 1 ~Ar 4 At least one of them has an ionic group. 1 and Y 2 Each independently represents a keto group or a protective group that can be derived into a keto group. * represents a bond with the general formula (S1) or other structural units. In addition, the ionic segment may also contain a structure other than the structure represented by the general formula (S1).
[0073] Here, as Ar 1 ~Ar 4 Preferred aromatic rings include hydrocarbon arylene groups such as phenylene, naphthylene, biphenylene, and fluorenediyl, and heteroarylene groups such as pyridinediyl, quinoxalinediyl, and thiophenediyl, but are not limited to these.
[0074] The ionic group used in the block copolymer of the present invention is preferably an atomic group having a negative charge, preferably a group having proton exchange ability. As such a functional group, preferably used are sulfonic acid group, sulfonimide group, sulfuric acid group, phosphonic acid group, phosphoric acid group, and carboxylic acid group as shown below.
[0075]
[0076] Such ionic groups include the case where the functional groups (f1) to (f7) above are in the form of salts. Examples of cations that form such salts include any metal cations, NR4 + (R is an arbitrary organic group) etc. are exemplified. The metal cation is not particularly limited, but Na, K, and Li are preferred because they are inexpensive and can easily undergo proton substitution.
[0077] The block copolymer may contain two or more of these ionic groups, and the combination is appropriately determined according to the polymer structure, etc. Among them, at least a sulfonic acid group, a sulfonimide group, and a sulfate group are more preferred from the perspective of high proton conductivity, and a sulfonic acid group is most preferred from the perspective of raw material cost.
[0078] The structure represented by the general formula (S1) of the block copolymer of the present invention is preferably represented by the following general formula (P1) from the viewpoints of dimensional stability and raw material availability, and is more preferably represented by the following general formula (S2) from the viewpoints of raw material availability and polymerizability.
[0079]
[0080] In the general formulas (P1) and (S2), Y 1 and Y 2 Each independently represents a keto group or a protective group capable of being derived into a keto group. 1 ~M 4 Each independently represents a hydrogen atom, a metal cation or an ammonium cation. n1 to n4 each independently represent 0 or 1, and at least one of n1 to n4 is 1. * represents a bond with the general formula (P1), (S2) or other structural units.
[0081] Furthermore, in view of raw material availability and polymerizability, n1=1, n2=1, n3=0, n4=0 or n1=0, n2=0, n3=1, n4=1 is most preferred.
[0082] The content of the structural unit represented by the general formula (S1) contained in the ionic segment is more preferably 20 mol % or more, further preferably 50 mol % or more, and most preferably 80 mol % or more.
[0083] Examples of the ionic monomer used to synthesize the above-mentioned ionic segment include aromatic active dihalide compounds.
[0084] As the aromatic active dihalide compound used in the ionic segment, it is preferred to use a compound in which an ionic acid group is introduced into the aromatic active dihalide compound from the perspective of chemical stability, manufacturing cost, and the ability to precisely control the amount of the ionic group. As suitable specific examples of monomers having a sulfonic acid group as an ionic group, 3,3'-disulfonate-4,4'-dichlorodiphenyl sulfone, 3,3'-disulfonate-4,4'-difluorodiphenyl sulfone, 3,3'-disulfonate-4,4'-dichlorodiphenyl ketone, 3,3'-disulfonate-4,4'-difluorodiphenyl ketone, 3,3'-disulfonate-4,4'-dichlorodiphenyl phenyl phosphine oxide, 3,3'-disulfonate-4,4'-difluorodiphenyl phenyl phosphine oxide, etc. can be cited, but it is not limited to these.
[0085] From the viewpoint of proton conductivity and hydrolysis resistance, the sulfonic acid group is most preferable as the ionic group, but the monomer having the above ionic group may have other ionic groups.
[0086] Among the above monomers having a sulfonic acid group, 3,3'-disulfonate-4,4'-dichlorophenyl ketone and 3,3'-disulfonate-4,4'-difluorophenyl ketone are more preferred from the viewpoint of chemical stability and physical durability, and 3,3'-disulfonate-4,4'-difluorophenyl ketone is most preferred from the viewpoint of polymerization activity.
[0087] As an ionic segment synthesized using 3,3'-disulfonate-4,4'-dichlorodiphenyl ketone and 3,3'-disulfonate-4,4'-difluorodiphenyl ketone as monomers having ionic groups, a structural unit represented by the following general formula (p1) is preferably used. The structure of the aromatic polyether polymer is a component that has excellent hot water resistance compared to the sulfone group in addition to the high crystallinity of the ketone group, and becomes an effective component for materials with excellent dimensional stability, mechanical strength, and physical durability under high temperature and high humidity conditions, so it is further preferably used. These sulfonic acid groups preferably become salts with univalent cationic species during polymerization. As univalent cationic species, sodium, potassium, other metal species, various amines, etc. can be used, but are not limited to these. These aromatic active dihalide compounds can be used alone, but multiple aromatic active dihalide compounds can also be used in combination.
[0088]
[0089] (In general formula (p1), M 1 and M 2 represents hydrogen, metal cation, or ammonium cation, and a1 and a2 represent integers of 1 to 4. The structural unit represented by the general formula (p1) may be arbitrarily substituted.
[0090] In addition, as an aromatic active dihalide compound, by copolymerizing a substance having an ionic group with a substance not having an ionic group, the ionic group density can also be controlled. However, as the above-mentioned ionic segment, from the viewpoint of ensuring the continuity of the proton conduction path, it is more preferred not to copolymerize an aromatic active dihalide compound not having an ionic group.
[0091] As more suitable specific examples of aromatic active dihalide compounds without ionic groups, 4,4'-dichlorodiphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 4,4'-dichlorodiphenyl ketone, 4,4'-difluorodiphenyl ketone, 4,4'-dichlorodiphenyl phenyl phosphine oxide, 4,4'-difluorodiphenyl phenyl phosphine oxide, 2,6-dichlorobenzonitrile, 2,6-difluorobenzonitrile, etc. can be cited. Among them, 4,4'-dichlorodiphenyl ketone and 4,4'-difluorodiphenyl ketone are more preferred from the perspective of imparting crystallinity, mechanical strength, physical durability, and hot water resistance, and 4,4'-difluorodiphenyl ketone is most preferred from the perspective of polymerization activity. These aromatic active dihalide compounds can be used alone, but multiple aromatic active dihalide compounds can also be used in combination.
[0092] As a polymer electrolyte material synthesized using 4,4'-dichlorophenyl ketone or 4,4'-difluorophenyl ketone as an aromatic active dihalide compound, it is preferably used to further include a constituent part represented by the following general formula (p2). This structural unit is a component that imparts intermolecular cohesion and crystallinity, and is a material having excellent dimensional stability, mechanical strength, and physical durability under high temperature and high humidity conditions, and is therefore preferably used.
[0093]
[0094] (The structural unit represented by the general formula (p2) may be arbitrarily substituted, but does not contain an ionic group.)
[0095] Examples of nonionic monomers used to synthesize the ionic segments include aromatic biphenol compounds, and aromatic biphenol compounds having a protective group as described below are particularly preferred. The monomers used to synthesize the ionic segments have been described above.
[0096] As an ionic segment, or as a structural unit constituting an ionic segment, as a preferred example of a structure that can be included in addition to the structure represented by the general formula (S1), there can be cited the structure of an aromatic polyether ketone copolymer composed of the structures represented by the following general formulas (T1) and (T2).
[0097]
[0098] In the general formulae (T1) and (T2), B represents a divalent organic group containing an aromatic ring. 5 and M 6 Each independently represents a hydrogen atom, a metal cation or an ammonium cation.
[0099] In the aromatic polyetherketone copolymer, the ion exchange capacity can be controlled by changing the composition ratio of the structural units represented by the general formulae (T1) and (T2).
[0100] Among them, ionic segments having structures represented by general formula (P1) and structures represented by general formulae (T1) and (T2) are particularly preferred. In such ionic segments, when the amounts of structural units represented by general formulae (P1), (T1) and (T2) are respectively represented by p1, t1 and t2, and the total molar amount of t1 and t2 is 100 parts by mole, p1 is preferably 75 parts by mole or more, more preferably 90 parts by mole or more, and even more preferably 100 parts by mole or more.
[0101] Examples of the divalent organic group B containing an aromatic ring in the general formulae (T1) and (T2) include residues of various divalent phenol compounds that can be used in the polymerization of aromatic polyether polymers by aromatic nucleophilic substitution reactions, and groups into which sulfonic acid groups are introduced.
[0102] Preferred specific examples of the divalent organic group B including an aromatic ring include groups represented by the following general formulae (X'-1) to (X'-6), but are not limited thereto.
[0103]
[0104] They may also have an ionic group or an aromatic group. In addition, they may also be used in combination as required. Among them, from the viewpoint of crystallinity, dimensional stability, toughness, and chemical stability, more preferably the group shown in the general formula (X'-1) to (X'-4), most preferably the group shown in the general formula (X'-2) and (X'-3).
[0105] [Nonionic segment]
[0106] The block copolymer of the present invention preferably has a structure in which the nonionic segment contains an aromatic polyether polymer. As the structure of the aromatic polyether polymer, for example, aromatic polyether, aromatic polyether ketone, aromatic polyether ether ketone, aromatic polyether ketone ketone, aromatic polyether ether ketone ketone, aromatic polyether ether ketone ketone, aromatic polyether ketone ether ketone ketone, aromatic polyether imide, and aromatic polyether sulfone are known, but the structure is not limited to these structures. The so-called aromatic polyether polymer has only to contain an aromatic group and an ether bond as a repeating unit.
[0107] It is more preferable that the structure of the aromatic polyether polymer contained in the nonionic segment constituting the block copolymer of the present invention is an aromatic polyether ketone polymer from the viewpoints of mechanical strength, dimensional stability and physical durability.
[0108] It is preferred that the nonionic segment constituting the block copolymer of the present invention has a structure represented by the following general formula (S3) from the viewpoints of dimensional stability, mechanical strength, and chemical stability.
[0109] *-Ar 5 -Y 3 -Ar 6 -O-Ar 7 -Y 4 -Ar 8 -O-* (S3)
[0110] In the general formula (S3), Ar 5 ~Ar 8 Each independently represents an arylene group. 5 ~Ar 8 None of them have ionic groups. 3 and Y 4 Each independently represents a keto group or a protective group capable of being derived into a keto group. * represents a bond to the general formula (S3) or other structural units.
[0111] Here, as Ar 5 ~Ar 8 Preferred aromatic rings include hydrocarbon arylene groups such as phenylene, naphthylene, biphenylene, and fluorenediyl groups, and heteroarylene groups such as pyridinediyl, quinoxalinediyl, and thiophenediyl groups, but are not limited thereto.
[0112] The nonionic segment constituting the block copolymer of the present invention preferably contains a structure represented by the following formula (P2) from the perspective of raw material availability. Among them, it is more preferred to contain a structural unit represented by the following formula (S4) from the perspective of mechanical strength, dimensional stability, and physical durability due to crystallinity.
[0113]
[0114] In the general formulas (P2) and (S4), Y 3 and Y 4 Each independently represents a keto group or a protective group capable of being derived into a keto group. * represents a bond to the general formula (P2) and (S4) or other structural units.
[0115] The content of the structure represented by the general formula (S3) or (S4) contained in the nonionic segment is preferably more, preferably 20 mol% or more, more preferably 50 mol% or more, and further preferably 80 mol% or more. When the content is 20 mol% or more, the effects of the present invention on mechanical strength, dimensional stability, and physical durability due to crystallinity can be fully obtained.
[0116] The block copolymer of the present invention is preferably composed of a block copolymer having an ionic segment containing a structural unit represented by the above general formula (S1) and a nonionic segment containing a structural unit represented by the above general formula (S3).
[0117] The nonionic segment is a segment showing crystallinity when containing the structural unit shown in the general formula (S3). The block copolymer comprising such a nonionic segment can be manufactured by deprotecting at least a portion of the protective group contained in the molded body after the block copolymer precursor having at least a protective group introduced into the nonionic segment is molded. For block copolymers, due to the tendency that the processability becomes poor by the crystallization of the polymer having a structural domain compared with random copolymers, it is preferred to introduce a protective group at least in the nonionic segment to improve processability, and about the ionic segment, it is also preferred to introduce a protective group when processability becomes poor.
[0118] Preferred examples of such a structural unit containing a protecting group include those containing at least one selected from the following general formulae (P3) and (P4).
[0119]
[0120] In formulas (P3) and (P4), Ar 11 ~Ar 14 represents any divalent arylene group, R 1 and R 2 represents at least one group selected from H and alkyl, R 3 represents an arbitrary alkylene group, and E represents O or S, each of which may represent two or more groups. The groups represented by formulae (P3) and (P4) may be arbitrarily substituted.
[0121] Among them, from the viewpoints of the odor, reactivity, stability, etc. of the compound, it is most preferred that in the above general formulas (P3) and (P4), E is O, that is, the ketone site is protected / deprotected with a ketal site.
[0122] As R in the general formula (P3) 1 and R 2 In terms of stability, an alkyl group is more preferred, an alkyl group having 1 to 6 carbon atoms is further preferred, and an alkyl group having 1 to 3 carbon atoms is most preferred. 3 In terms of stability, an alkylene group having 1 to 7 carbon atoms is more preferred, and an alkylene group having 1 to 4 carbon atoms is most preferred. 3 Specific examples include -CH2CH2-, -CH(CH3)CH2-, -CH(CH3)CH(CH3)-, -C(CH3)2CH2-, -C(CH3)2CH(CH3)-, -C(CH3)2O(CH3)2-, -CH2CH2CH2-, -CH2C(CH3)2CH2-, etc., but are not limited to these.
[0123] As Ar in the above general formulae (P3) and (P4) 11 ~Ar 14 The preferred organic group is phenylene, naphthylene, or biphenylene. They may be substituted arbitrarily. As the aromatic polyether polymer, from the perspective of solubility and ease of obtaining raw materials, Ar in the above general formula (P4) is more preferred. 13 and Ar 14 All are phenylene, most preferably Ar 13 and Ar 14 All are p-phenylene.
[0124] Here, as a method for protecting the ketone site with a ketal, a method of reacting a precursor compound having a ketone group with a monofunctional and / or bifunctional alcohol in the presence of an acid catalyst can be cited. For example, it can be produced by reacting a ketone precursor 4,4'-dihydroxybenzophenone with a monofunctional and / or bifunctional alcohol in a solvent such as an aliphatic or aromatic hydrocarbon in the presence of an acid catalyst such as hydrogen bromide. The alcohol is an aliphatic alcohol having 1 to 20 carbon atoms.
[0125] The improved process for making ketal monomers comprises reacting a ketone precursor, 4,4'-dihydroxybenzophenone, with a difunctional alcohol in the presence of an alkyl orthoester and a solid catalyst.
[0126] The method of deprotecting at least a part of the ketone site protected with ketal to convert it into a ketone site is not particularly limited. The above-mentioned deprotection reaction can be carried out in the presence of water and acid under non-uniform or uniform conditions, but from the viewpoint of mechanical strength, physical durability, and solvent resistance, a method of acid treatment after molding into a film or the like is more preferred. Specifically, the deprotection can be carried out by immersing the molded film in a hydrochloric acid aqueous solution or a sulfuric acid aqueous solution, and the concentration of the acid and the temperature of the aqueous solution can be appropriately selected.
[0127] The weight ratio of the necessary acidic aqueous solution to the polymer is preferably 1 to 100 times, but a larger amount of water may be used. The acid catalyst is preferably used at a concentration of 0.1 to 50% by weight of the water present. Suitable acid catalysts include strong inorganic acids such as hydrochloric acid, nitric acid, fluorosulfonic acid, and sulfuric acid, and strong organic acids such as p-toluenesulfonic acid and trifluoromethanesulfonic acid. The amount of the acid catalyst and excess water, the reaction pressure, etc. may be appropriately selected according to the film thickness of the polymer, etc.
[0128] For example, if the film has a thickness of 50 μm, it is possible to easily deprotect substantially all of the film by immersing it in an acidic aqueous solution such as exemplified by a 6N hydrochloric acid aqueous solution and heating it at 95° C. for 1 to 48 hours. In addition, even if it is immersed in a 1N hydrochloric acid aqueous solution at 25° C. for 24 hours, most of the protecting groups can be deprotected. However, the conditions for deprotection are not limited to these, and deprotection can also be performed using an acidic gas, an organic acid, or the like, or by heat treatment.
[0129] Even when the aromatic polyether polymer includes a bonding method other than an ether bond such as a direct bond, the position of the introduced protecting group is more preferably the aromatic ether polymer portion from the viewpoint of improving processability.
[0130] Specifically, for example, an aromatic polyether polymer containing structural units represented by the general formulae (P3) and (P4) can be synthesized by using compounds represented by the following general formulae (P3-1) and (P4-1) as aromatic biphenol compounds, respectively, through an aromatic nucleophilic substitution reaction with an aromatic active dihalide compound. The structural units represented by the general formulae (P3) and (P4) can be derived from either an aromatic biphenol compound or an aromatic active dihalide compound, but it is more preferable to use a substance derived from an aromatic biphenol compound in consideration of the reactivity of the monomer.
[0131]
[0132] In the general formulas (P3-1) and (P4-1), Ar 11 ~Ar 14 represents any divalent arylene group, R 1 and R 2 represents at least one group selected from H and alkyl, R 3 represents an arbitrary alkylene group, and E represents O or S. The compounds represented by the general formula (P3-1) and the general formula (P4-1) may be arbitrarily substituted. Preferred protecting groups have been described above.
[0133] [Detailed Description of Block Copolymer]
[0134] The block copolymer of the present invention is a segment chain that is incompatible with each other by more than two kinds, that is, a hydrophilic segment containing an ionic group and a hydrophobic segment not containing an ionic group are connected to form a substance of a polymer chain. In a block copolymer, by the short-range interaction produced by the repulsion between chemically different segment chains, phase separation is formed into a nano or micro domain consisting of each segment chain. Furthermore, since the segment chains are covalently bonded to each other, long-range interactions are generated, and by this effect, each domain has a specific order and is configured. The higher-order structure formed by the domain set consisting of each segment chain is referred to as a nano or micro phase separation structure. Here, the so-called domain refers to a block formed by the coagulation of similar segments in one or more polymer chains. Regarding the ionic conduction of a polymer electrolyte membrane, the spatial configuration of the ionic conductive segments in the membrane, that is, a nano or micro phase separation structure becomes important.
[0135] In the block copolymer of the present invention, the effect of the invention can be fully obtained by having the number average molecular weight Mn1 of the ionic segment exceeding 40,000. This is considered to be because as the number average molecular weight of the ionic segment increases, the cohesion of the segment when forming a phase separation structure increases, forming a phase separation structure suitable for proton conduction.
[0136] Regarding Mn1 and Mn2 of the block copolymer of the present invention, it is preferred that 2<Mn1 / Mn2<7 is satisfied because the block copolymerization reaction proceeds appropriately, a high molecular weight block copolymer can be obtained, and a phase separation structure suitable for proton conduction can be formed.
[0137] From the viewpoint of block copolymerizability and formation of a phase separation structure, it is more preferred that the relationship of 3≤Mn1 / Mn2<7 is further satisfied.
[0138] The block copolymer of the present invention preferably contains a linker site that connects the ionic segment and the nonionic segment. In the present invention, the linker is defined as a site that connects the ionic segment and the nonionic segment and has a chemical structure different from that of the ionic segment and the nonionic segment.
[0139] The linker connects different segments while suppressing randomization of the copolymer caused by the ether exchange reaction, segment breakage, and other side reactions that may occur during the synthesis of the copolymer. Therefore, by using a compound that provides such a linker as a raw material, a block copolymer can be obtained without reducing the molecular weight of each segment.
[0140] Preferred specific examples of the linker include decafluorobiphenyl, hexafluorobenzene, 4,4′-difluorodiphenyl sulfone, and 2,6-difluorobenzonitrile, but the present invention is not limited thereto.
[0141] In view of the balance between proton conductivity and water resistance, the ion exchange capacity of the block copolymer of the present invention is preferably 0.1 to 5 meq / g, more preferably 1.5 meq / g or more, most preferably 2 meq / g or more, more preferably 3.5 meq / g or less, most preferably 3 meq / g or less.
[0142] In view of the proton conductivity under low humidification conditions, the ion exchange capacity of the ionic segment is preferably high, preferably 2.5 meq / g or more, more preferably 3 meq / g or more, and further preferably 3.5 meq / g or more. In addition, it is preferably 6.5 meq / g or less, more preferably 5 meq / g or less, and further preferably 4.5 meq / g or less.
[0143] From the viewpoints of hot water resistance, mechanical strength, dimensional stability and physical durability, the ion exchange capacity of the nonionic segment is preferably low, preferably 1 meq / g or less, more preferably 0.5 meq / g, and further preferably 0.1 meq / g or less.
[0144] Here, the so-called ion exchange capacity is the molar amount of the ion exchange group introduced per unit dry weight of the block copolymer, polymer electrolyte material and polymer electrolyte membrane. The ion exchange capacity can be measured by elemental analysis, neutralization titration, etc. When the ion exchange group is a sulfonic acid group, elemental analysis can also be used, calculated by S / C ratio, but it is difficult to measure in the case of including a sulfur source other than the sulfonic acid group. Therefore, in the present invention, the ion exchange capacity is defined as the value obtained by the neutralization titration described later.
[0145] The block copolymer of the present invention preferably has a phase separation structure, and particularly preferably has a co-continuous phase separation structure. The block copolymer of the present invention having a phase separation structure means that the phase separation structure can be confirmed when a film-shaped body of the block copolymer is observed using a transmission electron microscope (TEM).
[0146] Phase separation structure can be formed by controlling the coagulation state and shape of ionic segments and nonionic segments. As the form of phase separation structure, cylindrical structure, sea island structure, layered structure, co-continuous structure can be cited. Wherein, in the case where the block copolymer has a co-continuous structure as a molded body, a three-dimensionally continuous proton conduction channel is formed, so that excellent proton conductivity can be achieved. In addition, since the nonionic hydrophobic segment also forms a three-dimensionally continuous structural domain, it has excellent fuel blocking, solvent resistance, dimensional stability, mechanical strength, and physical durability.
[0147] The block copolymer of the present invention is preferably observed by TEM at 50,000 times, and a phase separation structure is observed, and the average period size measured by image processing is more than 8nm and less than 300nm. Wherein, the average period size is more preferably more than 10nm and less than 200nm, and most preferably more than 15nm and less than 150nm. It should be noted that the so-called period size refers to the period length of the domain formed by the condensation of the ionic segment and the domain formed by the condensation of the nonionic segment.
[0148] [Method for producing block copolymer]
[0149] A specific method for synthesizing a block copolymer including an ionic segment and a nonionic segment is exemplified, but the present invention is not limited thereto.
[0150] Each segment used in the present invention is preferably synthesized by an aromatic nucleophilic substitution reaction because it is easy to process. The aromatic nucleophilic substitution reaction is a method of reacting a monomer mixture of a dihalide compound and a diol compound in the presence of a basic compound. The polymerization can be carried out at a temperature range of 0 to 350° C., but preferably at a temperature of 50 to 250° C.
[0151] The reaction can also be carried out under solvent-free conditions, but is preferably carried out in a solvent. As solvents that can be used, non-protonic polar solvents such as N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, cyclopentane, 1,3-dimethyl-2-imidazolidinone, hexamethylphosphoric triamide, etc. can be cited, but are not limited to these, as long as they are substances that can be used as stable solvents in aromatic nucleophilic substitution reactions. These organic solvents can be used alone or as a mixture of two or more.
[0152] As the alkaline compound, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, etc. can be cited, but as long as it is a substance that can make the diols into an active phenolate structure, it can be used without being limited to these. In addition, in order to improve the nucleophilicity of the phenolate, it is also suitable to add crown ethers such as 18-crown-6. Crown ethers are sometimes coordinated to the sodium ions and potassium ions of the sulfonic acid group to improve the solubility of the sulfonate part of the monomer or polymer in an organic solvent, and can be preferably used.
[0153] In the aromatic nucleophilic substitution reaction, water is sometimes generated as a by-product. At this time, no matter how the polymerization solvent is, toluene or the like can be coexisted in the reaction system and water can be removed from the system as an azeotrope. As a method for removing water from the system, a water absorbent such as a molecular sieve can also be used.
[0154] The block copolymer of the present invention can be prepared by deprotecting at least a portion of the protecting groups contained in the precursor after synthesizing the block copolymer precursor. As the method for preparing the block copolymer and the block copolymer precursor of the present invention, it is preferred to have at least the following steps (1) to (2). By having these steps, the improvement of mechanical strength and durability brought about by high molecular weight can be achieved, and by the alternating introduction of the two segments, a phase separation structure and a block copolymer with excellent low humidification proton conductivity in which the domain size is strictly controlled can be obtained.
[0155] (1) A step of introducing linker sites at both ends of one of an ionic segment having -OM groups (M represents a hydrogen atom, a metal cation or an ammonium cation) at both ends and a nonionic segment having -OM groups at both ends by reacting the -OM groups at both ends of the segment with a linker compound.
[0156] (2) A step of polymerizing the linker sites at both ends of the segment into which the linker site is introduced synthesized in (1) and the -OM groups at both ends of another segment to produce a block copolymer or a block copolymer precursor having an ionic segment and a nonionic segment.
[0157] As specific examples of the segment represented by the general formula (S1) in which both ends are -OM groups, and the segment represented by the general formula (S2) in which both ends are -OM groups, the segments of the structures represented by the following formulas (H3-1) and (H3-2) can be cited respectively. In addition, as structures in which the segments of the structures represented by the formulas (H3-1) and (H3-2) are reacted with halide linkers, for example, the structures represented by the following formulas (H3-3) and (H3-4) can be cited respectively. However, the present invention is not limited to these.
[0158]
[0159] In formulae (H3-1) to (H3-4), N1, N2, N3, and N4 each independently represent an integer of 1 to 200.
[0160] In formulas (H3-1) to (H3-4), the halogen atom is represented by F, the terminal -OM group is represented by -OK group, and the alkali metal is represented by Na and K, but it can be used without limitation. In addition, these formulas are inserted for the purpose of helping the reader to understand, and do not necessarily accurately represent the chemical structure, accurate composition, arrangement method, position, number, molecular weight, etc. of the polymer components of the polymer, and are not limited to these.
[0161] Furthermore, for formulas (H3-1) to (H3-4), although a ketal group is introduced as a protecting group in any segment, in the present invention, it is sufficient to introduce a protecting group in a component with high crystallinity and low solubility. Therefore, a protecting group is not necessarily required in the above-mentioned ionic segment, and from the viewpoint of physical durability and dimensional stability, a substance without a protecting group can be preferably used.
[0162] [Polymer electrolyte materials]
[0163] The polymer electrolyte material of the present invention is characterized in that it comprises the above block copolymer. By appropriately selecting the chemical structure, segment length, molecular weight, ion exchange capacity, etc. of the block copolymer of the present invention, it is possible to control various properties of the polymer electrolyte material, such as processability, domain size, crystallinity / amorphousness, mechanical strength, and proton conductivity.
[0164] [Polymer electrolyte molded body]
[0165] The block copolymer of the present invention is suitable as a polymer electrolyte material and can be processed into a polymer electrolyte molded body using the polymer electrolyte material. The form of the above-mentioned molded body is not particularly limited, and examples thereof include adhesives, fibers, films, rods, etc. of electrode catalyst layers. Among them, preferred films and adhesives are particularly preferred, and films are particularly preferred.
[0166] [Polymer electrolyte membrane]
[0167] The polymer electrolyte membrane of the present invention is characterized by being formed using a polymer electrolyte material containing the above-mentioned block copolymer.
[0168] When the block copolymer of the present invention is formed into a film, it can be a method of forming a film from a solution state at the stage of having a protective group such as ketal or a method of forming a film from a molten state, etc. For the former, for example, a method of dissolving the polymer electrolyte material in a solvent such as N-methyl-2-pyrrolidone, casting the solution on a glass plate, etc., and removing the solvent to form a film can be exemplified.
[0169] As the solvent used for film making, as long as the block copolymer is dissolved and then removed, it is suitable to use a non-protonic polar solvent such as N, N-dimethylacetamide, N, N-dimethylformamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, cyclopentane, 1,3-dimethyl-2-imidazolidinone, hexamethylphosphoric triamide, ester solvents such as γ-butyrolactone and butyl acetate, carbonate solvents such as ethylene carbonate and propylene carbonate, alkylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, or alcohol solvents such as isopropanol, water and mixtures thereof, but the solubility of non-protonic polar solvents is the highest and is preferred. In addition, in order to improve the solubility of the ionic segment, it is also suitable to add crown ethers such as 18-crown-6.
[0170] In the present invention, when a block copolymer is used for solution membrane formation, the selection of a solvent is important for the phase separation structure, and a mixture of an aprotic polar solvent and a low-polarity solvent is also a suitable method.
[0171] The polymer solution modulated to the necessary solid content concentration is supplied to the filtration or pressure filtration under normal pressure, and the foreign matter existing in the polymer electrolyte solution is removed to obtain a tough film and a preferred method. The filter material used here is not particularly limited, but glass filters and metallic filters are suitable. In this filtration, the pore size of the smallest filter through which the polymer solution passes is preferably less than 1 μm.
[0172] As a method for converting the block copolymer of the present invention into a polymer electrolyte membrane, for example, after a membrane composed of the block copolymer is prepared by the above method, at least a portion of the site protected by the protecting group is deprotected. For example, in the case of having a ketal site as a protecting group, at least a portion of the ketone site protected by the ketal is deprotected to become a ketone site. According to this method, a solution membrane of a block copolymer lacking solubility can be formed, and proton conductivity, mechanical strength, and physical durability can be combined.
[0173] In addition, the following process may be performed: after the electrolyte membrane is formed in a state where the contained ionic groups and the cations of the alkali metal or alkaline earth metal form a salt, the cations of the alkali metal or alkaline earth metal are exchanged with protons. This process is preferably a process in which the formed membrane is contacted with an acidic aqueous solution, and more preferably a process in which the formed membrane is immersed in an acidic aqueous solution. In this process, the protons in the acidic aqueous solution are replaced with the cations ionically bonded to the ionic groups, and at the same time, the residual water-soluble impurities, residual monomers, solvents, residual salts, etc. are removed.
[0174] The acidic aqueous solution is not particularly limited, but preferably sulfuric acid, hydrochloric acid, nitric acid, acetic acid, trifluoromethanesulfonic acid, methanesulfonic acid, phosphoric acid, citric acid, etc. The temperature, concentration, etc. of the acidic aqueous solution should also be appropriately determined. From the viewpoint of productivity, it is preferred to use a sulfuric acid aqueous solution of 3 mass % or more and 30 mass % or less at a temperature of 0° C. or more and 80° C. or less.
[0175] The thickness of the polymer electrolyte membrane in the present invention is preferably 1 μm or more in order to obtain mechanical strength and physical durability of the membrane for practical use, and preferably 2,000 μm or less in order to reduce membrane resistance, that is, to improve power generation performance. The further preferred range of the membrane thickness is 3 μm or more and 200 μm or less. The membrane thickness can be controlled by the solution concentration or the coating thickness on the substrate.
[0176] Furthermore, the polymer electrolyte membrane of the present invention may contain additives such as a crystal nucleating agent, a plasticizer, a stabilizer, an antioxidant, or a release agent commonly used for polymer compounds within a range not adversely affecting the purpose of the present invention.
[0177] In addition, the polymer electrolyte membrane formed by the block copolymer obtained by the present invention can contain various polymers, elastomers, fillers, microparticles, various additives, etc., in order to improve mechanical strength, thermal stability, processability, etc., within the range that does not adversely affect the above-mentioned characteristics. In addition, the polymer electrolyte membrane can be reinforced with a microporous membrane, a nonwoven fabric, a mesh, etc.
[0178] The block copolymer of the present invention can be applied to a variety of purposes by being made into a polymer electrolyte molded body and a polymer electrolyte membrane as a polymer electrolyte material. For example, it can be applied to medical uses such as artificial skin, filtration uses, ion exchange resin uses such as chlorine-resistant reverse osmosis membranes, various structural material uses, electrochemical uses, humidification membranes, antifogging films, antistatic films, deoxidation membranes, solar cell films, and gas barrier films. Among them, it can be more preferably used in various electrochemical uses. As electrochemical uses, for example, solid polymer fuel cells, redox flow batteries, water electrolysis devices, chlor-alkali electrolysis devices, electrochemical hydrogen pumps, and water electrolysis hydrogen generation devices can be cited.
[0179] In solid polymer fuel cells, electrochemical hydrogen pumps, and water electrolysis hydrogen generation devices, polymer electrolyte membranes are used as structures in which catalyst layers, electrode substrates, and separators are sequentially stacked on both sides. Among them, the material (i.e., the material of the layer of catalyst layer / electrolyte membrane / catalyst layer) that makes the catalyst layer stacked on both sides of the electrolyte membrane is called an electrolyte membrane (CCM) with a catalyst layer, and the material (i.e., the material of the layer of gas diffusion substrate / catalyst layer / electrolyte membrane / catalyst layer / gas diffusion substrate) that makes the catalyst layer and the gas diffusion substrate sequentially stacked on both sides of the electrolyte membrane is called a membrane electrode complex (MEA). The block copolymer of the present invention is particularly suitable for use as a polymer electrolyte membrane constituting such CCM and MEA.
[0180] The catalyst layer-carrying electrolyte membrane of the present invention is characterized by being constituted by using the above-mentioned polymer electrolyte membrane using a polymer electrolyte material containing the above-mentioned block copolymer.
[0181] The membrane electrode assembly of the present invention is characterized by being constituted by using the above-mentioned polymer electrolyte membrane using a polymer electrolyte material containing the above-mentioned block copolymer.
[0182] The solid polymer fuel cell of the present invention is characterized by being constituted using the above-mentioned polymer electrolyte membrane using a polymer electrolyte material containing the above-mentioned block copolymer.
[0183] The water electrolysis type hydrogen generation device of the present invention is characterized by being constituted using the above-mentioned polymer electrolyte membrane using a polymer electrolyte material containing the above-mentioned block copolymer.
[0184] Example
[0185] (1) Molecular weight of polymer
[0186] The number average molecular weight and weight average molecular weight of the polymer were measured by GPC. As an integrated device of ultraviolet absorption detector and differential refractive index detector, HLC-8022GPC manufactured by Tosoh Corporation was used, and as a guard column, TSKgel Guard Column Super H-H manufactured by Tosoh Corporation (inner diameter 4.6 mm, length 3.5 cm) was used, and as a GPC column, two TSKgel Super HM-H manufactured by Tosoh Corporation (inner diameter 6.0 mm, length 15 cm) were used. The measurement was performed in N-methyl-2-pyrrolidone solvent (N-methyl-2-pyrrolidone solvent containing 10 mmol / L of lithium bromide) at a sample concentration of 0.1 wt%, a flow rate of 0.2 mL / min, a temperature of 40°C, and a measurement wavelength of 265 nm, and the number average molecular weight and weight average molecular weight were calculated by standard polystyrene conversion.
[0187] (2) Ion exchange capacity (IEC)
[0188] The measurement was performed by the neutralization titration method shown in the following 1] to 4]. The measurement was performed three times and the average value was taken.
[0189] 1] After proton substitution, the block copolymer was thoroughly washed with pure water and the water was wiped off, and then vacuum dried at 100° C. for 12 hours or more, and the dry weight was determined.
[0190] 2] 50 mL of a 5 wt % sodium sulfate aqueous solution was added to the block copolymer, and the mixture was allowed to stand for 12 hours to perform ion exchange.
[0191] 3] The generated sulfuric acid was titrated using a 0.01 mol / L sodium hydroxide aqueous solution. A commercially available phenolphthalein solution for titration at 0.1 w / v% was added as an indicator, and the point at which the solution turned light reddish purple was defined as the end point.
[0192] 4]IEC is obtained by the following formula.
[0193] IEC (meq / g) = [concentration of sodium hydroxide aqueous solution (mmol / mL) x amount added (mL)] / dry weight of sample (g).
[0194] (3) Dry and wet dimensional change rate
[0195] The electrolyte membrane (specimen) was cut into a 3mm×20mm rectangle to prepare a sample piece. The sample holder was set in a thermomechanical analyzer TMA / SS6100 (manufactured by Hitachi Hightech Science) with a furnace with a temperature and humidity adjustment function in such a way that the long side of the sample piece became the measurement direction, and was set in such a way that a stress of 20mN was applied. In the furnace, the sample was stabilized at 23°C and 50%RH for 1 hour, and the length of the sample piece was set to zero. The temperature in the furnace was fixed at 23°C, and the humidity was adjusted to 30%RH (drying condition) after 30 minutes and maintained for 20 minutes. Next, the humidity was adjusted to 90%RH (humidification condition) after 30 minutes. The dry-wet cycle (30%RH-90%RH) was set as 1 cycle, and the difference between the dimensional change rate (%) of 30%RH and the dimensional change rate (%) of 90%RH in the 10th cycle was set as the dry-wet dimensional change rate (%).
[0196] (4) Observation of phase separation structure using transmission electron microscopy (TEM)
[0197] The sample was immersed in a 2 wt% aqueous solution of lead acetate as a staining agent and placed at 25°C for 72 hours. The dyed sample was taken out and embedded with epoxy resin. An ultra-thin slicer was used to cut a thin slice of 80 nm at room temperature, and the obtained thin slice was recovered on a Cu grid for TEM observation. The observation was carried out at an accelerating voltage of 100 kV, and the photography was carried out in a manner of ×20,000 and ×40,000 as a photo magnification. As an instrument, HT7700 (manufactured by Hitachi Hi-Tech) was used.
[0198] (5) Observation of phase separation structure using transmission electron microscopy (TEM) tomography
[0199] The sheet sample prepared by the method described in (4) above was mounted on a collodion film and observed under the following conditions.
[0200] Equipment: Field emission electron microscope (HRTEM) JEM 2100F manufactured by JEOL Ltd.
[0201] Image acquisition: Digital Micrograph (Gatan)
[0202] System: Notation
[0203] Accelerating voltage: 200 kV
[0204] Shooting magnification: 30,000 times
[0205] Tilt angle: +60°~-62°
[0206] Reconstruction resolution: 0.71nm / pixel.
[0207] The marking method was applied to the 3D reconstruction. Au colloidal particles applied to the collodion film were used as alignment marks for the 3D reconstruction. Using the marks as a reference, CT reconstruction was performed based on a total of 124 TEM images obtained from a series of continuous tilt images in which the sample was tilted every 1° in the range of +61° to -62°, and the 3D phase separation structure was observed.
[0208] (6) Evaluation of power generation performance
[0209] In order to evaluate the power generation performance, an electrolyte membrane (CCM) with a catalyst layer and a membrane electrode assembly (MEA) were produced in the following manner.
[0210] <CCM production>
[0211] The following anode catalyst decal was stacked on one surface of the electrolyte membrane, and the cathode catalyst decal was stacked on the other surface, and hot-pressed at 150° C. and 5 MPa for 3 minutes to bond them. Then, the polytetrafluoroethylene films of the catalyst decals were peeled off to obtain CCM.
[0212] <Production of anode catalyst decal>
[0213] 10 parts by mass of platinum catalyst-loaded carbon particles TEC10E50E (platinum loading rate 50% by mass) manufactured by Tanaka Precious Metals Industries, Ltd. and 5 parts by mass of a fluorine-based polymer electrolyte ("NAFION" (registered trademark) manufactured by Kemazu Co., Ltd.) in terms of solid content were dispersed in a mixed solvent (water and 1-propanol in a mass ratio of 4:6) using a bead mill to prepare a catalyst ink 1 having a solid content concentration of 10% by mass. The catalyst ink 1 was applied to a commercially available polytetrafluoroethylene film and dried to produce an anode catalyst decal. The amount of platinum in the catalyst layer was 0.4 mg / cm 2 .
[0214] <Production of cathode catalyst decal>
[0215] The amount of platinum in the catalyst layer was changed to 0.7 mg / cm 2 , except for this, the same operation as the anode catalyst decal was performed.
[0216] <MEA production>
[0217] A commercially available gas diffusion layer 24BCH manufactured by SGL was superimposed on both surfaces of the CCM produced above, and hot pressed at 160° C. and 4.5 Ma for 5 minutes to produce an MEA. The power generation performance of this MEA was evaluated in the following manner.
[0218] <Evaluation of power generation performance>
[0219] The MEA was placed in a JARI standard cell "Ex-1" (electrode area 25 cm 2 ) and set up as a power generation evaluation module. Hydrogen was supplied to the anode electrode as fuel gas, and air was supplied to the cathode electrode as oxidizing gas. Power generation evaluation was performed under the following conditions, from 0A / cm 2 To 1.2A / cm 2 The current was swept until the voltage became below 0.2V.
[0220] In the present invention, the current density is read as 1.2A / cm 2 The voltage at that time was evaluated.
[0221] Electronic load device: Electronic load device "PLZ664WA" manufactured by Kikusui Electronics Industry Co., Ltd.
[0222] Unit temperature: 60℃
[0223] Relative humidity of supply gas (hydrogen and air): 40% RH (low humidification condition), 80% RH (high humidification condition)
[0224] Back pressure of supply gas (hydrogen and air): 150 kPa
[0225] Gas utilization rate: 70% of the measured gas at the anode and 40% of the measured gas at the cathode.
[0226] Synthesis Example 1 (Synthesis of 2,2-bis(4-hydroxyphenyl)-1,3-dioxolane (K-DHBP) represented by the following formula (G1))
[0227] In a 500 mL flask equipped with a stirrer, a thermometer, and a distillation tube, 49.5 g of 4,4'-dihydroxybenzophenone, 134 g of ethylene glycol, 96.9 g of trimethyl orthoformate, and 0.50 g of p-toluenesulfonic acid monohydrate were added to prepare a solution. Then, the mixture was stirred at 78-82°C for 2 hours. Furthermore, the internal temperature was slowly raised to 120°C and maintained at 120°C until the distillation of methyl formate, methanol, and trimethyl orthoformate completely stopped. After the reaction solution was cooled to room temperature, the reaction solution was diluted with ethyl acetate. The organic layer was washed with 100 mL of 5% potassium carbonate aqueous solution and separated, and the solvent was distilled off. 80 mL of dichloromethane was added to the residue to precipitate crystals, which were filtered and dried to obtain 52.0 g of 2,2-bis(4-hydroxyphenyl)-1,3-dioxolane. The purity was 99.9%.
[0228]
[0229] Synthesis Example 2 (Synthesis of 3,3'-disulfonated-4,4'-difluorobenzophenone disodium salt represented by the following formula (G2))
[0230] 109.1 g of 4,4'-difluorobenzophenone (Aldrich reagent) was reacted in 150 mL of fuming sulfuric acid (50% SO3) (Wako Pure Chemical Industries, Ltd. reagent) at 100°C for 10 hours. Then, it was added little by little to a large amount of water, neutralized with NaOH, and 200 g of salt (NaCl) was added to precipitate the synthetic product. The obtained precipitate was separated by filtration and recrystallized with an ethanol aqueous solution to obtain 3,3'-disulfonated-4,4'-difluorobenzophenone disodium salt. The purity was 99.3%.
[0231]
[0232] Synthesis Example 3 (Synthesis of 3,3'-disulfonic acid sodium salt-4,4'-difluorodiphenyl sulfone represented by the following formula (G3))
[0233] 109.1 g of 4,4-difluorodiphenyl sulfone (Aldrich reagent) was reacted in 150 mL of fuming sulfuric acid (50% SO3) (Wako Pure Chemical Industries, Ltd. reagent) at 100°C for 10 hours. Then, it was added little by little to a large amount of water, neutralized with NaOH, and 200 g of salt was added to precipitate the synthetic product. The obtained precipitate was separated by filtration and recrystallized with ethanol aqueous solution to obtain 3,3'-disulfonic acid sodium salt-4,4'-difluorodiphenyl sulfone. The purity was 99.3%.
[0234]
[0235] Example 1
[0236] (Synthesis of nonionic oligomer a1 represented by the following general formula (G4))
[0237] In a 2,000 mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 16.59 g of potassium carbonate (Aldrich reagent, 120 mmol), 25.83 g of K-DHBP obtained in Synthesis Example 1 (100 mmol), and 20.73 g of 4,4'-difluorobenzophenone (Aldrich reagent, 95 mmol) were added. After nitrogen substitution in the apparatus, 300 mL of N-methylpyrrolidone (NMP) and 100 mL of toluene were added, and after dehydration at 150°C, the temperature was raised to remove the toluene, and polymerization was carried out at 170°C for 3 hours. Reprecipitation and purification were carried out in a large amount of methanol to obtain the terminal hydroxyl body of the nonionic oligomer a1. The number average molecular weight of the terminal hydroxyl body of the nonionic oligomer a1 is 9,000.
[0238] In a 500mL three-necked flask equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 1.1g of potassium carbonate (Aldrich reagent, 8mmol) and 9.0g (1mmol) of the terminal hydroxyl body of the above-mentioned nonionic oligomer a1 were added. After nitrogen substitution in the device, 100mL of NMP and 30mL of toluene were added, and after dehydration at 100°C, the toluene was removed by heating. Furthermore, 1.1g of hexafluorobenzene (Aldrich reagent, 6mmol) was added, and the reaction was carried out at 105°C for 12 hours. The nonionic oligomer a1 (terminal: fluorine group) shown in the following formula (G4) was obtained by reprecipitation with a large amount of isopropanol. The number average molecular weight of the nonionic oligomer a1 is 10,000.
[0239]
[0240] (Synthesis of Ionic Oligomer a2 Represented by the Following Formula (G5))
[0241] In a 2,000 mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 27.64 g of potassium carbonate (Aldrich reagent, 200 mmol), 12.91 g (50 mmol) of K-DHBP obtained in Synthesis Example 1, 9.31 g of 4,4'-biphenol (Aldrich reagent, 50 mmol), 41.60 g (98.5 mmol) of 3,3'-disulfonated-4,4'-difluorobenzophenone disodium salt obtained in Synthesis Example 2, and 26.40 g of 18-crown-6 (100 mmol of Wako Pure Chemical Industries, Ltd.) were added. After nitrogen substitution in the apparatus, 300 mL of NMP and 100 mL of toluene were added, dehydration was performed at 150° C., the temperature was raised to remove toluene, and polymerization was performed at 170° C. for 6 hours. The product was purified by reprecipitation with a large amount of isopropanol to obtain an ionic oligomer a2 (terminal: hydroxyl group) represented by the following formula (G5). The number average molecular weight of the ionic oligomer a2 was 45,000. In the formula (G5), M represents a hydrogen atom, Na or K.
[0242]
[0243] (Synthesis of Block Copolymer b1 Containing Oligomer a2 as Ionic Segment and Oligomer a1 as Nonionic Segment)
[0244] In a 2000mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 49.0g of an ionic oligomer a2 and 12.3g of a nonionic oligomer a1 were added, and NMP was added in such a manner that the total amount of the oligomers added was 7wt%, and the reaction was carried out at 105°C for 24 hours. Reprecipitation was carried out into a large amount of isopropanol / NMP mixed solution (weight ratio 2 / 1), and a large amount of isopropanol was used for purification to obtain a block copolymer b1. The number average molecular weight of the block copolymer b1 was 160,000, and the weight average molecular weight was 400,000.
[0245] The 20 wt % NMP solution in which the obtained block copolymer b1 was dissolved was filtered under pressure through a glass fiber filter, then cast on a glass substrate and dried at 100 ° C for 4 hours to obtain a film-like molded body. The molded body was immersed in a 10 mass % sulfuric acid aqueous solution at 80 ° C for 24 hours, and after proton substitution and deprotection reaction, it was immersed in a large excess of pure water for 24 hours and fully washed to obtain a polymer electrolyte membrane A (film thickness 10 μm). By TEM and TEM tomography observation, it was confirmed that the phase separation structure of the co-continuous type was confirmed, and the hydrophilic domain containing the ionic group and the hydrophobic domain not containing the ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 14.8 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0246] Example 2
[0247] (Synthesis of Block Copolymer b2 Containing Oligomer a2 as Ionic Segment and Oligomer a1 as Nonionic Segment)
[0248] Block copolymer b2 was obtained in the same manner as in the synthesis of block copolymer b1 except that the reaction time of ionic oligomer a2 and nonionic oligomer a1 was changed to 32 hours. The number average molecular weight of block copolymer b2 was 190,000 and the weight average molecular weight was 440,000.
[0249] Block copolymer b2 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane B (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 15.6 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0250] Example 3
[0251] (Synthesis of Block Copolymer b3 Containing Oligomer a2 as Ionic Segment and Oligomer a1 as Nonionic Segment)
[0252] Block copolymer b3 was obtained in the same manner as in the synthesis of block copolymer b1 except that the reaction time of ionic oligomer a2 and nonionic oligomer a1 was changed to 16 hours. The number average molecular weight of block copolymer b3 was 120,000 and the weight average molecular weight was 340,000.
[0253] Block copolymer b3 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane C (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 13.3 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0254] Example 4
[0255] (Synthesis of nonionic oligomer a3 represented by formula (G4))
[0256] A hydroxy-terminated oligomer a3 was obtained in the same manner as in the synthesis of the hydroxy-terminated oligomer a1 except that the amount of 4,4′-difluorobenzophenone used was changed to 20.51 g. The hydroxy-terminated oligomer a3 had a number average molecular weight of 7,000.
[0257] A nonionic oligomer a3 (terminal: fluorine group) represented by formula (G4) was obtained in the same manner as in the synthesis of oligomer a1 except that 7.0 g of the terminal hydroxyl group of oligomer a3 was used instead of the terminal hydroxyl group of oligomer a1. The number average molecular weight of the nonionic oligomer a3 was 8,000.
[0258] (Synthesis of Block Copolymer b4 Containing Oligomer a2 as Ionic Segment and Oligomer a3 as Nonionic Segment)
[0259] Block copolymer b4 was obtained in the same manner as in the synthesis of block copolymer b1 except that nonionic oligomer a3 (7.65 g) was used instead of nonionic oligomer a1 (12.3 g). Block copolymer b4 had a number average molecular weight of 160,000 and a weight average molecular weight of 400,000.
[0260] Block copolymer b4 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane D (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 6.7 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0261] Example 5
[0262] (Synthesis of nonionic oligomer a4 represented by formula (G4))
[0263] A hydroxy-terminated oligomer a4 was obtained in the same manner as in the synthesis of the hydroxy-terminated oligomer a1 except that the amount of 4,4′-difluorobenzophenone used was changed to 20.99 g. The hydroxy-terminated oligomer a4 had a number average molecular weight of 11,000.
[0264] A nonionic oligomer a4 (terminal: fluorine group) represented by formula (G4) was obtained in the same manner as in the synthesis of oligomer a1 except that 11.0 g of the terminal hydroxyl group of oligomer a4 was used instead of the terminal hydroxyl group of oligomer a1. The number average molecular weight of the nonionic oligomer a3 was 12,000.
[0265] (Synthesis of Ionic Oligomer a5 Represented by Formula (G5))
[0266] Ionic oligomer a5 was obtained in the same manner as in the synthesis of ionic oligomer a2 except that the amount of 3,3′-disulfonated-4,4′-difluorobenzophenone disodium salt used was 41.72 g (98.8 mmol). The number average molecular weight of this ionic oligomer a5 was 48,000.
[0267] (Synthesis of Block Copolymer b5 Containing Oligomer a5 as Ionic Segment and Oligomer a4 as Nonionic Segment)
[0268] Block copolymer b5 was obtained in the same manner as in the synthesis of block copolymer b1 except that nonionic oligomer a4 (12.3 g) was used instead of nonionic oligomer a1 (12.3 g). Block copolymer b5 had a number average molecular weight of 160,000 and a weight average molecular weight of 400,000.
[0269] Block copolymer b5 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane E (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 15.8 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0270] Example 6
[0271] (Synthesis of Block Copolymer b6 Containing Oligomer a5 as Ionic Segment and Oligomer a1 as Nonionic Segment)
[0272] Block copolymer b6 was obtained in the same manner as the synthesis of block copolymer b1 except that ionic oligomer a5 (49.0 g) was used instead of ionic oligomer a2 (49.0 g) and nonionic oligomer a1 (7.65 g) was used instead of nonionic oligomer a1 (12.3 g). The number average molecular weight of block copolymer b6 was 160,000 and the weight average molecular weight was 400,000.
[0273] Block copolymer b6 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane F (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 7.2 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0274] Example 7
[0275] (Synthesis of Ionic Oligomer a6 Represented by Formula (G5))
[0276] Ionic oligomer a6 was obtained in the same manner as in the synthesis of ionic oligomer a2 except that the amount of 3,3′-disulfonated-4,4′-difluorobenzophenone disodium salt used was 41.50 g (98.3 mmol). The number average molecular weight of this ionic oligomer a6 was 43,000.
[0277] (Synthesis of Block Copolymer b7 Containing Oligomer a6 as Ionic Segment and Oligomer a3 as Nonionic Segment)
[0278] Block copolymer b7 was obtained in the same manner as the synthesis of block copolymer b1 except that ionic oligomer a6 (49.0 g) was used instead of ionic oligomer a2 (49.0 g) and nonionic oligomer a3 (12.3 g) was used instead of nonionic oligomer a1 (12.3 g). The number average molecular weight of block copolymer b7 was 160,000 and the weight average molecular weight was 400,000.
[0279] Block copolymer b7 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane G (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 12.9 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0280] Example 8
[0281] (Synthesis of nonionic oligomer a7 represented by the following formula (G6))
[0282] A nonionic oligomer a10 with a terminal hydroxyl group was obtained in the same manner as in the synthesis of the nonionic oligomer a1 except that 23.21 g of 4,4-difluorodiphenyl sulfone was used instead of 4,4′-difluorobenzophenone. The number average molecular weight of the nonionic oligomer a10 with a terminal hydroxyl group was 7,000.
[0283] The same operation as the synthesis of nonionic oligomer a1 was carried out except that the terminal hydroxyl group of nonionic oligomer a7 (7.0 g) was used instead of the terminal hydroxyl group of nonionic oligomer a1 to obtain nonionic oligomer a7 (terminal fluorine group) represented by formula (G6). The number average molecular weight of this nonionic oligomer a7 was 8,000.
[0284]
[0285] (Synthesis of Ionic Oligomer a8 Represented by the Following Formula (G7))
[0286] In a 2,000 mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 27.6 g of potassium carbonate (Aldrich reagent, 200 mmol), 12.9 g (50 mmol) of K-DHBP obtained in the above-mentioned Synthesis Example 1, 9.3 g (50 mmol) of 4,4'-biphenol, and 44.66 g (98.1 mmol) of 3,3'-disulfonic acid sodium salt-4,4'-difluorodiphenylsulfone obtained in Synthesis Example 3 were added. After nitrogen substitution in the apparatus, 300 mL of NMP and 100 mL of toluene were added, and after dehydration at 130° C., the temperature was raised to remove toluene, and polymerization was carried out at 165° C. for 5 hours. The product was purified by reprecipitation with a large amount of isopropanol to obtain an ionic oligomer a8 (terminal hydroxyl group) represented by formula (G10). The number average molecular weight of the ionic oligomer a8 was 42,000.
[0287]
[0288] (Synthesis of Block Copolymer b8 Containing Oligomer a8 as Ionic Segment and Oligomer a7 as Nonionic Segment)
[0289] Block copolymer b8 was obtained in the same manner as the synthesis of block copolymer b1 except that ionic oligomer a8 (49.0 g) was used instead of ionic oligomer a2 (49.0 g) and nonionic oligomer a7 (12.3 g) was used instead of nonionic oligomer a1 (12.3 g). The number average molecular weight of block copolymer b8 was 160,000 and the weight average molecular weight was 410,000.
[0290] Block copolymer b8 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane H (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, no crystallization peak was confirmed. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0291] Comparative Example 1
[0292] (Synthesis of Ionic Oligomer a9 Represented by Formula (G5))
[0293] Ionic oligomer a9 was obtained in the same manner as in the synthesis of ionic oligomer a2 except that the amount of 3,3′-disulfonated-4,4′-difluorobenzophenone disodium salt used was 41.38 g (98.0 mmol). The number average molecular weight of this ionic oligomer a9 was 38,000.
[0294] (Synthesis of Block Copolymer b9 Containing Oligomer a9 as Ionic Segment and Oligomer a1 as Nonionic Segment)
[0295] Block copolymer b9 was obtained in the same manner as in the synthesis of block copolymer b1 except that ionic oligomer a9 (49.0 g) was used instead of ionic oligomer a2 (49.0 g). Block copolymer b9 had a number average molecular weight of 160,000 and a weight average molecular weight of 400,000.
[0296] Block copolymer b9 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane I (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 15.1 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0297] Comparative Example 2
[0298] (Synthesis of Block Copolymer b10 Containing Oligomer a9 as Ionic Segment and Oligomer a3 as Nonionic Segment)
[0299] Block copolymer b10 was obtained in the same manner as the synthesis of block copolymer b1 except that ionic oligomer a9 (49.0 g) was used instead of ionic oligomer a2 (49.0 g) and nonionic oligomer a3 (7.65 g) was used instead of nonionic oligomer a1 (12.3 g). The number average molecular weight of block copolymer b10 was 160,000 and the weight average molecular weight was 420,000.
[0300] Block copolymer b10 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane J (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 7.0 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0301] Comparative Example 3
[0302] (Synthesis of Ionic Oligomer a10 Represented by Formula (G5))
[0303] Ionic oligomer a10 was obtained in the same manner as in the synthesis of ionic oligomer a2 except that the amount of 3,3′-disulfonated-4,4′-difluorobenzophenone disodium salt used was 41.34 g (97.9 mmol). The number average molecular weight of the ionic oligomer a10 was 35,000.
[0304] (Synthesis of Block Copolymer b11 Containing Oligomer a10 as Ionic Segment and Oligomer a3 as Nonionic Segment)
[0305] Block copolymer b11 was obtained in the same manner as the synthesis of block copolymer b1 except that ionic oligomer a10 (49.0 g) was used instead of ionic oligomer a2 (49.0 g), and nonionic oligomer a3 (12.3 g) was used instead of nonionic oligomer a1 (12.3 g). The number average molecular weight of block copolymer b11 was 160,000, and the weight average molecular weight was 400,000.
[0306] Block copolymer b11 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane K (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed, and the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 13.1 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0307] Comparative Example 4
[0308] (Synthesis of block copolymer b12 containing oligomer a2 as an ionic segment and oligomer a1 as a nonionic segment)
[0309] In a 2000mL SUS polymerization apparatus equipped with a stirrer, a nitrogen inlet tube, and a Dean-Stark trap, 49.0 g of an ionic oligomer a2 and 12.3 g of a nonionic oligomer a1 were added, and NMP was added in such a manner that the total amount of the oligomers added was 5 wt%, and the reaction was carried out at 95°C for 14 hours. Reprecipitation was carried out into a large amount of isopropanol / NMP mixed solution (weight ratio 2 / 1), and a large amount of isopropanol was used for purification to obtain a block copolymer b1. The number average molecular weight of the block copolymer b12 was 70,000, and the weight average molecular weight was 220,000.
[0310] Block copolymer b12 was used instead of block copolymer b1. In addition, a polymer electrolyte membrane L (film thickness 10 μm) was obtained by the same method as in Example 1. By TEM and TEM tomography observation, a co-continuous phase separation structure was confirmed. Although the hydrophilic domain containing an ionic group and the hydrophobic domain not containing an ionic group formed a continuous phase, a part was discontinuous and an uneven structure was observed. By DSC, a crystallization peak was confirmed, and the heat of crystallization was 10.3 J / g. In addition, no crystalline peak (crystallinity 0%) was confirmed by wide-angle X-ray diffraction. The results are shown in Table 1.
[0311] [Table 1]
[0312]
[0313] Industrial Availability
[0314] The block copolymer of the present invention is made into a polymer electrolyte molded body and a polymer electrolyte membrane as a polymer electrolyte material, so that it can be applied to a variety of purposes. For example, it can be applied to medical uses such as artificial skin, filtration uses, ion exchange resin uses such as chlorine-resistant reverse osmosis membranes, various structural material uses, electrochemical uses, humidification membranes, antifogging films, antistatic films, deoxidation membranes, solar cell films, and gas barrier films. It can be more preferably used in various electrochemical uses. As electrochemical uses, for example, solid polymer fuel cells, redox flow batteries, water electrolysis devices, chlor-alkali electrolysis devices, electrochemical hydrogen pumps, and water electrolysis hydrogen generation devices can be cited. The block copolymer of the present invention is made into a polymer electrolyte membrane constituting CCM and MEA and is particularly suitable for solid polymer fuel cells and water electrolysis hydrogen generation devices.
Claims
1. A block copolymer having one or more segments containing ionic groups and one or more segments not containing ionic groups, wherein the segments containing ionic groups are hereinafter referred to as "ionic segments" and the segments not containing ionic groups are hereinafter referred to as "non-ionic segments", wherein the ionic segments are aromatic hydrocarbon polymers having a number average molecular weight of more than 40,000 and less than 50,000, and when the number average molecular weight of the ionic segments is Mn1, the number average molecular weight of the non-ionic segments is Mn2, and the number average molecular weight of the block copolymer is Mn3, the relationship of Mn3 / (Mn1+Mn2)>1.5 is satisfied. 2 . The block copolymer according to claim 1 , wherein the heat of crystallization of the block copolymer measured by differential scanning calorimetry is 0.1 J / g or more, or the degree of crystallinity of the block copolymer measured by wide-angle X-ray diffraction is 0.5% or more. The block copolymer according to claim 1 or 2, wherein the aromatic hydrocarbon polymer is an aromatic polyether polymer. The block copolymer according to claim 3 , wherein the aromatic polyether polymer is an aromatic polyether ketone polymer.
5. The block copolymer according to claim 1 or 2, characterized in that The block copolymer has a linker site that connects the ionic segment and the nonionic segment. The block copolymer according to claim 1 or 2, which has a relationship of 2<Mn1 / Mn2<7.
7. The block copolymer according to claim 1, wherein the ionic segment comprises a structure represented by the following general formula (S1): *——On 1 -Y 1 -On 2 -From-On 3 -Y 2 -On 4 -O—* (S1) In the general formula (S1), Ar 1 ~Ar 4 Each independently represents a substituted or unsubstituted arylene group, Ar 1 ~Ar 4 At least one of them has an ionic group; 1 and Y 2 Each independently represents a keto group or a protective group capable of being derived into a keto group; * represents a bond to the general formula (S1) or other structural units.
8. The block copolymer according to claim 7, wherein the structure represented by the general formula (S1) is the structure represented by the following general formula (S2), In the general formula (S2), Y 1 and Y 2 Each independently represents a keto group or a protecting group capable of being derived into a keto group; M 1 ~M 4 Each independently represents a hydrogen atom, a metal cation or an ammonium cation; n1 to n4 are each independently 0 or 1, and at least one of n1 to n4 is 1; * represents a bond with the general formula (S2) or other structural units. 9 . The block copolymer according to claim 1 , wherein the nonionic segment comprises an aromatic polyether polymer. 10 . The block copolymer according to claim 9 , wherein the aromatic polyether polymer is an aromatic polyether ketone polymer.
11. The block copolymer according to claim 1, wherein the nonionic segment comprises a structure represented by the following general formula (S3): *-On 5 -Y 3 -On 6 -From-On 7 -Y 4 - On 8 -O* (S3) In the general formula (S3), Ar 5 ~Ar 8 Each independently represents an arylene group; wherein Ar 5 ~Ar 8 None of them have ionic groups; Y 3 and Y 4 Each independently represents a keto group or a protective group capable of being derived into a keto group; * represents a bond to the general formula (S3) or other structural units.
12. The block copolymer according to claim 11, wherein the structure represented by the general formula (S3) is the structure represented by the following general formula (S4), In the general formula (S4), Y 3 and Y 4 Each independently represents a keto group or a protective group capable of being derived into a keto group; * represents a bond to the general formula (S4) or other structural units. The block copolymer according to claim 1 , which has a co-continuous phase separation structure. 14 . A polymer electrolyte material comprising the block copolymer according to claim 1 . 15 . A polymer electrolyte molded body comprising the polymer electrolyte material according to claim 14 . 16 . A polymer electrolyte membrane formed using the polymer electrolyte material according to claim 14 .
17. An electrolyte membrane with a catalyst layer, which is constituted by using the polymer electrolyte membrane according to claim 16.
18. A membrane electrode assembly, which is constituted by using the polymer electrolyte membrane according to claim 16.
19. A solid polymer fuel cell, which is constructed using the polymer electrolyte membrane according to claim 16.
20. A water electrolysis type hydrogen generation device, which is constructed using the polymer electrolyte membrane according to claim 16.
Citation Information
Patent Citations
Polymer electrolyte, and polymer electrolyte membrane using same, membrane-electrode assembly and fuel cell using same
JP2007109638A
Aromatic sulfonic acid derivative, sulfonic acid group-containing polymer, block copolymer, polymer electrolyte material, polymer electrolyte molded body, and solid polymer fuel cell
WO2013002274A1